Characterization of particle confinement properties in RFX-mod at a high plasma current. (27th March 2015) - Auriemma, F.; Lorenzini, R.; Agostini, M.; Carraro, L.; Masi, G. De; Fassina, A.; Gobbin, M.; Martines, E.; Innocente, P.; Scarin, P.; Schneider, W.; Zuin, M.
Abstract: Transport phenomena affect the performance of fusion devices, reducing heat and particle confinement and consequently leading to a lower fusion triple product and higher fluxes on the plasma facing material. Special attention is devoted in the fusion community to the study of transport mitigation phenomena which lead to the onset of transport barriers in tokamaks, stellarators and reverse field pinch plasmas. The aim of this study is to deepen our understanding of the mechanisms driving transport in the presence of electron internal transport barriers in the RFX-mod single helical axis (SHAx) state (Lorenzini et al 2009 Nature Phys. 5 570). We discuss whether transport in the core can be described within the theory of chaotic transport. Light is also shed on the mechanisms acting at the plasma edge. The particle source is calculated using the 2D Monte-Carlo code NENE, considering the pattern of plasma–wall interaction. In the core region of the SHAx we found that the diffusivity along 90% of the radius is reduced with respect to the standard case: D  ∼ 1 m 2  s −1 fits well with the density profile, compared with the ∼50 m 2  s −1 of a standard plasma. This result confirms a strong mitigation of magnetic chaos, although comparison with the neoclassical diffusivity D neo  ∼ 0.01–0.4 m 2  s −1 indicates that transport in the SHAx is still anomalous. The same picture describes well both the particle and energy transport in the plasma core: comparison with the effective thermal diffusivity χ eff indicates that the ratio χ eff / D  ∼ ( m i / m e ) 0.5 is consistent with the theory of chaos-dominated transport. The plasma edge is affected by a different mechanism. In the external region (the final 10% of the radius) magnetic chaos is suppressed and the edge diffusivity is likely to be ruled by electrostatic turbulence, in particular a direct link with the presence of pressure coherent structures is found.